2015
DOI: 10.1517/14728222.2015.1101067
|View full text |Cite
|
Sign up to set email alerts
|

Targets to treat metabolic syndrome in polycystic ovary syndrome

Abstract: Introduction Metabolic syndrome is comprised of a combination of the following states: increased insulin resistance, dyslipidemia, cardiovascular disease, and increased abdominal obesity. Women with polycystic ovary syndrome (PCOS) have an increased risk of developing metabolic syndrome over the course of their lives. Metabolic syndrome increases risk of major cardiovascular events, morbidity, quality of life, and overall health care costs. Though metabolic syndrome in women with PCOS is an area of great conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 173 publications
(147 reference statements)
0
29
0
8
Order By: Relevance
“…38,48,49 Results from five meta-analyses of RCTs with women with PCOS supported the benefits of LSM programs on decreased BMI, fasting blood glucose, IR, FSH, sex hormone-binding globulin (SHBG), total testosterone, androstenedione, free androgen index (FAI) and Ferriman-Gallwey (FG) score and improved cardiorespiratory fitness, but not on glucose tolerance or lipid profiles. 57,63,[70][71][72] No studies have assessed the effects of LSM programs on clinical reproductive outcomes, quality of life or treatment satisfaction in women with PCOS.…”
Section: Lsm Programs and Pcosmentioning
confidence: 97%
See 3 more Smart Citations
“…38,48,49 Results from five meta-analyses of RCTs with women with PCOS supported the benefits of LSM programs on decreased BMI, fasting blood glucose, IR, FSH, sex hormone-binding globulin (SHBG), total testosterone, androstenedione, free androgen index (FAI) and Ferriman-Gallwey (FG) score and improved cardiorespiratory fitness, but not on glucose tolerance or lipid profiles. 57,63,[70][71][72] No studies have assessed the effects of LSM programs on clinical reproductive outcomes, quality of life or treatment satisfaction in women with PCOS.…”
Section: Lsm Programs and Pcosmentioning
confidence: 97%
“…5,[47][48][49][50] CC is the first-line therapy for ovulation induction in anovulatory infertile women with PCOS, although almost 20% of patients are unresponsive. 47,51 Results from a three-arm randomized, parallel, controlled, assessor-blinded clinical trial investigating the effects of a 6-week intervention with structured exercise training and hypocaloric diet on probability of ovulation after CC in overweight and obese CC-resistant PCOS women showed that structured exercise training combined with hypocaloric diet was effective in increasing the response to CC and the ovulation rate in overweight and obese PCOS patients.…”
Section: Options For Pcos Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, PCOS is the most common cause of anovulatory infertility, the morphological changes may be genetic, but ovulation or anovulation is mainly dependent on the follicular environment, may be due to excessive production of local endocrine factor [18,28,29]. Hyperandrogenism is one of the diagnostic criteria of PCOS, and ovarian hyperandrogenism can lead to excessive follicular atresia, follicular stasis and anovulation.…”
Section: Ovarian Dysfunctionmentioning
confidence: 99%